Beyond Creating Collections: A Scoping Review of 3D Heritage Storytelling - Basaraba, Nicole (My University, 2024)
This paper aims to demonstrate how virtual reality (VR), augmented reality (AR), and 3D archaeological reconstructions have been employed to immerse viewers into historical places with the inclusion or exclusion of digital narratives in the heritage and tourism sectors. Countless galleries, libraries, archives, and museums have included digitally re-created objects and re-imagined scenes in situ through theatrical sets and live historical re-enactments to help visitors see and contextualise objects from history. What if these techniques were applied to 3D virtual narrative experiences? This scoping review focuses primarily on selected studies that create 3D models for archaeology, VR, and AR that utilise 3D models, and virtual heritage ‘edutainment’ experiences published within the last five years (i.e., 2018-2023). It gives an overview of the current methods and technologies used to create 3D heritage productions for scientific studies, heritage preservation and tourism, and educational applications. Ultimately, this paper discusses possibilities for future work on how extended reality and 3D models could be included in narrative experiences based on gaps in the existing research. Keywords
Digital Humanities in the Nordic and Baltic Countries 8th Conference
Keywords: 3D archaeology, 3D heritage, cultural heritage, digital storytelling, virtual reality, augmented reality, gamification, edutainment; Digital Humanities; Digital Humanities; Interdisciplinary research; digital narratives, digital storytelling, transmedia, cultural heritage